Peran Optimasi Media TI dalam Pembelajaran Pendidikan Agama Kristen di SMP N 1 Ledo - Esterani, Esterani; Theodorus, Theodorus; Resti, Resti; Weldy, Weldy; Dandi, Dandi (INTELEKTIUM, 2024)
The use of IT-based media in education systems has continuously risen, and the digital era has provided a great opportunity to integrate any media in the process of learning. This research will present an assessment of the role of optimized IT media in CRE at SMP N 1 Ledo. A qualitative approach with the case study method is used to gain depth into how IT media influences the learning process in this particular context. The findings of the case study reveal that IT media implementation increased both student activity and enhanced learning achievements of students in the subject of CRE. Furthermore, IT-based media make learning more interactive and fun for students; in this way, students can manage to retain concentration and sustain motivation throughout the entire learning process. Secondly, it has been indicated that IT media has to be duly developed and maintained if it is ever going to serve its full purpose in the classroom. If no support is given from time to time and technical developments are not made, the effectiveness of IT media might be rendered gradually useless. It also confirms that teachers need sufficient training and support so that they would feel confident in their contribution to students via the integration of technology into teaching. Capability of easily combining traditional approaches with the aid of digital tools generally increases the level of learning. The results of this research then demonstrate that IT media is capable of enhancing the effectiveness of Christian Religious Education, especially in making learning more interactive and fun for students. They also indicate the necessity for continuous professional development of teachers themselves so that teachers are able to keep up with the times and make use of these facilities appropriately in teaching